Association between changes in knee load and effusion-synovitis: evidence of mechano-inflammation in knee osteoarthritis using high tibial osteotomy as a model. Issue 2 (February 2021) - Atkinson, H.F.; Birmingham, T.B.; Primeau, C.A.; Schulz, J.M.; Appleton, C.T.; Pritchett, S.L.; Giffin, J.R.
Summary: Objective: Although mechanically-induced inflammation is an appealing explanation linking different etiologic factors in osteoarthritis (OA), clinical research investigating changes in both biomechanics and joint inflammation is limited. The purpose of this study was to evaluate the association between change in surrogate measures of knee load and knee effusion-synovitis in patients with medial compartment knee OA undergoing high tibial osteotomy (HTO). Methods: Thirty-six patients with medial compartment knee OA and varus alignment underwent 3D gait analysis and 3T magnetic resonance imaging (MRI) preoperatively and 1 year after medial opening wedge HTO. Primary outcome measures were the change in the external knee adduction moment impulse during walking and change in knee suprapatellar effusion-synovitis volume manually segmented on MRI by one blinded assessor. Results: Mean (SD) knee adduction moment impulse [24.0 (6.5) Nms] and knee effusion-synovitis volume [8976.7 (8016.9) mm 3 ] suggested substantial preoperative medial knee load and inflammation. 1-year postoperative changes in knee adduction moment impulse [−10.1 Nms (95%CI: −12.7, −7.4)], and knee effusion-synovitis volume [−1856 mm 3 (95%CI: −3830, 117)] were positively correlated [ r = 0.60 (95% CI 0.34, 0.78)]. Simple linear regression suggested a 448 mm 3 (95%CI: 241, 656) reduction in knee effusion-synovitis volume per 1 Nms reduction in knee adduction moment impulse. Change in knee adduction moment impulse explained 36% ( R 2 = 0.36) of the variance of change in knee effusion-synovitis volume. Conclusions: Reduction in medial knee load is positively associated with reduction in knee inflammation after HTO, suggesting the phenomenon of mechano-inflammation in patients with knee OA.